Diabetic ketoacidosis: nursing resident's perception of the multidisciplinary approach in the emergency room - Lotici , Gisele (2023)
Currently, diabetes mellitus (DM) emerges as one of the main challenges in the field of public health, both due to its high prevalence in the population, which results in functional disabilities and deaths, and the significant financial burden imposed on the government for the control and treatment of complications related to this disease. In the context of complications associated with DM, the occurrence of Diabetic Ketoacidosis (DKA) stands out, an emergency clinical condition that is more prevalent in individuals affected by type 1 DM. DKA is characterized by the presence of ketonemia, metabolic acidosis and hyperglycemia. Considering a clinical emergency, the objective of this article is to report the perception, as a nursing resident, about the management of patients with diabetic ketoacidosis in the emergency room. It is noteworthy that, at the beginning of care, it is essential that the nurse performs a good physical examination and collects personal information and daily lifestyle information from family members and/or guardians, since early conduct makes a total difference in the outcome of the condition. clinical.